General Criticism if Language in Sehah AL- Gohary - الطائي, يحيى خليل اسماعيل (Al-Adab Journal, 2019)
I found outthrough my reading to multitude of dictionaries for their use(Colloquialism language) while they talk about the word or installation here and there.This research deals with the concept of (colloquialism) by the both ancient and modern writers, also it talks about the book that dealt with this kind of language through Al-jawhari book (Al-sehah), It is almost more dictionaries revenue for this public explanation of the language in both criticism and explication.So,this research discussed what Al-jawhari mentioned in his book, and made a comparison between his thoughts and both ancient and modern writers' thoughts mentioned in their dictionaries, and then he registered the difference and compatibility.